VIP's of the Philippine business. (Mahal Kong Pilipinas, 1991)
This book provides the list of influential people in Philippine business. Divided into six chapters, it features well-known business executives, actors, architects, conglomerates, and other professionals who have excelled in their field. The Philippine's richest personalities--the billionaires- are also included, with brief personal data. Arranged alphabetically, pictures of the personalities are also featured. This book provides the list of influential people in Philippine business. Divided into six chapters, it features well-known business executives, actors, architects, conglomerates, and other professionals who have excelled in their field. The Philippine's richest personalities--the billionaires- are also included, with brief personal data. Arranged alphabetically, pictures of the personalities are also featured.